Analisis Faktor yang Mempengaruhi Ketimpangan Pendapatan: Studi Komparatif Kawasan Indonesia Barat, Timur, Indonesia - Lailatussubha, Mutiara; Nazer, M (SAFE-Network, 2025)
In 2022, income inequality in Indonesia continued to show significant regional disparities, with Eastern Indonesia recording a Gini ratio of 0.346, higher than that of Western Indonesia at 0.345. This difference indicates that income distribution in the eastern region remains more uneven compared to the western region, highlighting the need for special attention to the underlying factors of inequality in both regions. Income inequality remains a major issue that hinders inclusive and sustainable development, particularly amid economic and social disparities between regions. This study aims to analyze the effects of financial inclusion, economic growth, education, and unemployment on income inequality in Western and Eastern Indonesia during the period 2008–2022. A quantitative approach is employed using the Random Effect Model panel data regression, with data processing conducted using STATA software. The results of the Random Effect Model regression show that in Western Indonesia, financial inclusion and economic growth have a positive and significant effect on income inequality, while education has a negative and significant effect, and unemployment does not have a significant impact. In Eastern Indonesia, education and unemployment have a negative and significant effect on income inequality, financial inclusion has a positive and significant effect, while economic growth does not affect income inequality in the region.